2022
DOI: 10.1155/2022/5595781
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of NADPH Oxidase-Dependent Early Oxidative and Inflammatory Responses in Chronic Obstructive Pulmonary Disease by Puerarin

Abstract: In the present study, we investigated effects of Puerarin on the early oxidative and inflammatory responses in the lung triggered by acute cigarette smoking (ACS). C57BL/6 mice were exposed to ACS for 1 hr in the presence or absence of Puerarin and harvested at 2, 6, and 24 hours. ACS induced significant increases in superoxide production in mouse lungs at 2 and 6 hours; and superoxide production was also elevated in a time and concentration dependent manner in cigarette smoke extract (CSE) stimulated human sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…CYBB, also referred to as NOX2, is mainly expressed in lung macrophages (Seimetz et al, 2020). And NOX2 protein expression is found to be upregulated in the lungs of COPD mice and is involved in the oxidative and inflammatory response in the early stages of COPD (Zhang et al, 2022). Heat shock protein (HSP) is a potent inducer of natural and adaptive immunity, and the association between increased expression levels of HSPB1 and the risk of COPD has been reported and verified (Cui et al, 2015).…”
Section: Discussionmentioning
confidence: 89%
“…CYBB, also referred to as NOX2, is mainly expressed in lung macrophages (Seimetz et al, 2020). And NOX2 protein expression is found to be upregulated in the lungs of COPD mice and is involved in the oxidative and inflammatory response in the early stages of COPD (Zhang et al, 2022). Heat shock protein (HSP) is a potent inducer of natural and adaptive immunity, and the association between increased expression levels of HSPB1 and the risk of COPD has been reported and verified (Cui et al, 2015).…”
Section: Discussionmentioning
confidence: 89%
“…In addition to some of these molecular targeted drugs, natural compounds, traditional Chinese medicine formulations, and some anti-inflammatory agents also inhibit the progression of COPD by inhibiting the PI3K/Akt pathway. It has been shown recently that puerarin can relieve over-oxidation in cells ( Zhang P. et al, 2022 ). Wang L. et al (2022) found that puerarin reverses apoptosis in HBEC stimulated by cigarette smoke extract (CSE) via the PI3K/Akt signaling pathway.…”
Section: Potential Drug Targeting Pi3k/akt For Copdmentioning
confidence: 99%
“…The fixed lung samples were embedded in paraffin as previously described [26], and sectioned serially at 5 μm slices by using a rotary microtome (Leica, Nussloch, Germany). Subsequently, the samples were stained with hematoxylin and eosin (H&E) [27,28]. Finally, the stained sections were observed and photographed under a BX53 microscope (Olympus, Tokyo, Japan).…”
Section: Morphological Analysis Of Lung Tissuementioning
confidence: 99%